Local Infiltration Anesthesia in Drainage of Quinsy - Farooq, Muhammad (International Journal of Pathology, 2018)
Peritonsillar abscess (PTA) or Quinsy is a severe form of infection which is rare but has a significant morbidity and mortality.Objectives: Present study was aimed to find out significance of local infiltration anesthesia (LIA) in drainage of quinsy.Materials and Methods: This prospective and comparative study was conducted to find the role of local infiltration anaesthesia (LIA) in fifty (50) patients of quinsy who were randomly divided into two equal groups. Group-A did not receive any local anaesthesia while Group-B received local infiltration anesthesia (LIA) for drainage of quinsy. The pain experienced by patients of both groups before, during and half an hour after the operation was measured on a numerical rating scale (NRS) from zero to 10. All the patients were followed-up for six weeks and other findings like need of hospitalisation, relief of trismus, rate of recovery and treatment cost were also recorded.Results: The Group-B patients felt less or no pain as compared to Group-A, who felt more pain during and after drainage of quinsy.Conclusion: Local infiltration anaesthesia has significant benefit in reducing pain during and after drainage of quinsy. It also enhances the rate of recovery, is more cost effective and less distressing for the patients.